2015
DOI: 10.1002/pip.2619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the compositional ratio distribution with sulfurization temperatures in the absorber layer on the defect and surface electrical characteristics of Cu2ZnSnS4 solar cells

Abstract: Although Cu2ZnSnS4 (CZTS) has attracted attention as an alternative absorber material to replace CuInGaSe2 (CIGS) in solar cells, the current level of understanding of its characteristic loss mechanisms is not sufficient for achieving high power conversion efficiency. In this study, which aimed to minimize the characteristic losses across the devices, we examined the relations between the compositional ratio distribution in the absorber layer, subsequent defect formation, and surface electrical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…Interestingly, we were able to observe SnO 2 phases near the Mo/CZTSSe interface; the SnO 2 peak intensity was higher near the MoSe 2 area, which indicated that Sn was reacting with oxygen from an unknown source. One of the most likely O sources, according to our previous studies, is SLG, which contains Na, Si, O, and so forth. We have already verified that the content of O in CZTS thin films diffused from SLG substrates is sufficient to be detected by secondary ion mass spectrometry (SIMS) and affect thin‐film fabrication .…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Interestingly, we were able to observe SnO 2 phases near the Mo/CZTSSe interface; the SnO 2 peak intensity was higher near the MoSe 2 area, which indicated that Sn was reacting with oxygen from an unknown source. One of the most likely O sources, according to our previous studies, is SLG, which contains Na, Si, O, and so forth. We have already verified that the content of O in CZTS thin films diffused from SLG substrates is sufficient to be detected by secondary ion mass spectrometry (SIMS) and affect thin‐film fabrication .…”
Section: Resultsmentioning
confidence: 76%
“…the SnO 2 peak intensity was higher near the MoSe 2 area, which indicated that Sn was reacting with oxygen from an unknown source. One of the most likely O sources, according to our previous studies, 11,27,44 is SLG, which contains Na, Si, O, and so forth.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The progresses in these routes showed that the use of metallic stacks provides for the moment better efficiencies at least for the selenide compounds, with University of Oldenburg (EHF/LCP group) reporting 11.4% [9], IREC 11.8% [6] and DGIST a 12.6% efficiency device [7]. Furthermore, a certified efficiency of 13.04% has been obtained using sputtered precursors [10], whereas for pure sulfide kesterite compounds the best results are instead obtained using S-containing targets [19] and/or cosputtering approach.…”
Section: Sequential Sputtering/co-sputteringmentioning
confidence: 99%